Pengaruh Jarak Tanam Antar Barisan pada Sistem Tumpangsari Beberapa Varietas Jagung Manis dengan Kacang Merah Terhadap Pertumbuhan dan Hasil - Ainun Marliah; Jumini Jumini; Jamilah Jamilah (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
The Effect of Spacing Between Rows of Several Varieties of Sweet Corn and Kidney Beans Growth and Yield for Intercropping SystemABSTRACT. The research was to find the effect of planting distance and some varieties on intercropping system of sweet corn and kidney beans to improve growth and yield. The experimental design was Complete Block Randomized with two factors and two replications. The first factor was planting distance between rows of sweet corn intercropping system (J1=60cmx30cm; J2=80cmx30cm; J3=100cmx30cm). Then the second factor was variety (V1= Kumala F1; V2= King Sweet F1; V3=Super Bee). The results indicated that the best planting distance on intercropping some varieties of sweet corn and kidney bean was 100cmx30cm for sweet corn and 80cmx30cm and 100cmx30cm for kidney bean. The varieties treatment showed that the best variety of sweet corn was Super Bee and kidney bean was King Sweet F1. There was significantly different interaction between planting distance and varieties on intercropping system of sweet and kidney bean on the corn husk weight of sweet corn.